2017
DOI: 10.1371/journal.pone.0169502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Silver-Embedded Ceramic Tablet as a Primary and Secondary Point-of-Use Water Purification Technology in Limpopo Province, S. Africa

Abstract: The World Health Organization (WHO) recognizes point-of-use water treatment (PoUWT) technologies as effective means to improve water quality. This paper investigates long-term performance and social acceptance of a novel PoUWT technology, a silver-infused ceramic tablet, in Limpopo Province, South Africa. When placed in a water storage container, the silver-embedded ceramic tablet releases silver ions into water, thereby disinfecting microbial pathogens and leaving the water safe for human consumption. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
(50 reference statements)
2
26
0
Order By: Relevance
“…Additionally, the ceramic technology was distributed with locally available 22 L plastic buckets that had lids and spigots to reduce the risk of recontamination during retrieval of water. The cubes were produced at a facility at the University of Virginia according to the method described by Ehdaie et al [33]. To disinfect 5-15 L of water, the ceramic cubes were placed in a bucket of water for at least eight hours.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the ceramic technology was distributed with locally available 22 L plastic buckets that had lids and spigots to reduce the risk of recontamination during retrieval of water. The cubes were produced at a facility at the University of Virginia according to the method described by Ehdaie et al [33]. To disinfect 5-15 L of water, the ceramic cubes were placed in a bucket of water for at least eight hours.…”
Section: Methodsmentioning
confidence: 99%
“…In follow-up studies conducted in communities where CWFs were distributed, it was found that in one Sri Lankan tsunami response community, 23% of people were using the ceramic filter three months after distribution, in the Dominican Republic, 48.7% of households were correctly operating filters 16 months after distribution with 54% of water samples from operating filters (26.1% of total) free of thermo-tolerant coliform [29,30]. Ehdaie [31], reported that 63% ceramic water filter-treated samples had < 1 CFU/100mL of E-coli after 1 year. Average percent reduction of E-coli among ceramic water filter households declined to 60% after 52 weeks, which is lower than what has previously been seen in long-term ceramic water filter studies.…”
Section: Ease Of Technologymentioning
confidence: 99%
“…These anti-microbial agents are able to add value of improving the killing efficacy of the ceramic water filter [4]. A study by van der Laan et al [13] showed that there was no difference in removing pathogens in ceramic water filters with silver and without silver nanoparticles.…”
Section: Data Is Average Of Triplicatesmentioning
confidence: 99%
“…In rural areas due to lack of awareness and maintenance, most of the families carry out the routine activities such as clothes washing, utensil washing, bathing cattle's, washing near to the ground and river water sources which is one of the reasons for contamination [3]. Close to 2 billion people over the world lack access to safe drinking water and estimated 2 million fatalities are linked to water borne infections [4]. Safe drinking water is very important in controlling and preventing many diseases.…”
Section: Introductionmentioning
confidence: 99%